Efektifitas Penggunaan Kompres Metronidazol dan NaCl 0,9% terhadap Penyembuhan Luka Diabetik di RSUD Margono Soekarjo Purwokerto - Supriyatin; Saryono; Latifah, Lutfatul (Jurnal Keperawatan Soedirman, 2007)
Diabetic wound needs continous nursing intervention, therefore healing process can effectively achieved There are some solutions used to care diabetic wound such as NaCL 0.9%, metronidazole, bee honey however until now there is no study shows effectiveness of those solutions. This study aims to compare effectiveness of Metronidazole and NaCL 0.9% to diabetic wound healing which include its wound dimension, odor, secretion, and granulation growth. This comparative study used Qusi Experimental Method and Non Ã‚Â¬Equivalent Control Group Design. Population was patiens cared in Kenanga and Teratai (Surgical Medical Ward) In-patient Department, Margono Soekarjo General Hospital Purwokerto. This study recruited 20 people as sample from July to September 2006 based on order of admission, odd numbers, were given metronidazole compress and even numbers were given NaCL 0.9% compress on their wound management. Prior to statistical test, data had been comprehensively tested and had fulfilled normal distribution requirements with Leve\'n test then \"t\" test 2n non-correlated and Chi-square were applied Statistical test shows that there was no difference between effectiveness of Metronidazole and NaCL 0.9% use. There was no difference for wound dimension reduction. Towards its granulation growth, on NaCL 0.9% was 2 respondents (20%) meanwhile on Metronidazole cared wound showed 60% out of 5 patients. On wound secretion reduction, 4 respondents cared with NaCL 0.9% still had \"much\" secretion and the remaining 16 respondents cared with both solutions had \"relative much\". Its effect to diabetic wound specific odor could be smelled from 1 meter distance (less odor) was 7 patients (70%) cared with NaCL 0.9% and 3 people used Metronidazole. For no odor had 8 respondents 7 people among them treated with Metronidazole. In conclusion for wound odor and wound secretion indicators show that wound treated with Metronidazole have a better performance than those cared with NaCL 0.9% although it is not statistically significant. On the other hand wound dimension and granulation growth for wound managed by both solutions have simply minor change.